The synergistic influence of spiritual leadership and mindfulness on organisational behaviour: insights from the Buddhist college context - Chandra Chandra; Nagian Toni; Elly Romy (International Journal of Science and Applied Science: Conference Series, 2025)
This study investigates the synergistic influence of spiritual Leadership and mindfulness on organisational behaviour within the context of a private Buddhist college in Medan, Indonesia. Drawing upon theories of leadership, mindfulness, and organisational behaviour, the research employs a quantitative associative design involving 25 respondents, comprising lecturers and administrative staff. Data were collected through standardised questionnaires that measured validated dimensions of spiritual Leadership, mindfulness, and organisational behaviour. The findings demonstrate that spiritual Leadership exerts a positive and significant impact on organisational behaviour, affirming the role of vision, altruistic love, and hope/faith in enhancing intrinsic motivation and organisational commitment. Likewise, mindfulness shows a positive and significant effect, supporting the proposition that conscious awareness, emotional regulation, and empathy foster more harmonious workplace interactions. Together, these variables explain 58% of the variance in organisational behaviour. The results highlight the importance of integrating spiritual values with psychological competencies to build a positive organisational culture. Practically, the study suggests that higher education institutions grounded in religious values should incorporate spiritual leadership development and mindfulness training as strategic interventions to promote harmony, resilience, and productivity within academic environments.